DIGITAL THEATER EXPERIMENTATIONS WITH HIGH SCHOOL STUDENTS (Revista NUPEART, 2021)
This text is the result of research on the Master of Arts course at the Arts Institute of the XX, which aimed to investigate and reflect on the processes of digital theatrical experimentation with high school students in a public school belonging to the Secretariat of State of Education of the Federal District. In the meantime, the target school has long discussed the use of contemporary digital technologies as facilitators of the meaningful teaching and learning process. From the developments in question, the research suggested a Pedagogical Proposal linking the teaching of Theater with contemporary digital technologies, making the reflection on the school processes concerned, based on five artistic products created by the students.
Keywords: Theater. Technology. Education. Aesthetics.